2017
DOI: 10.1029/2017eo068325
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Highest-Temperature Extremes in the Antarctic

Abstract: The record high temperature for regions south of 60°S latitude is a balmy 19.8°C (67.6°F), recorded 30 January 1982 at a research station on Signy Island.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…The present study confirms the suggestion (de los Milagros Skansi et al, 2017) that the record high temperature at Signy Research Station on 30th January 1982 was caused by a combination of exceptional warm air advection together with additional warming resulting from a local föhn effect. Situated immediately downwind of the Coronation Island mountain chain, Signy Island was directly in the path of adiabatically warmed air descending from around summit level.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The present study confirms the suggestion (de los Milagros Skansi et al, 2017) that the record high temperature at Signy Research Station on 30th January 1982 was caused by a combination of exceptional warm air advection together with additional warming resulting from a local föhn effect. Situated immediately downwind of the Coronation Island mountain chain, Signy Island was directly in the path of adiabatically warmed air descending from around summit level.…”
Section: Discussionsupporting
confidence: 91%
“…By contrast, Grytviken station on the subantarctic island of South Georgia, 900 km to the northeast of Signy Island, recorded a station record maximum temperature of 22.9 ∘ C on 31st January 1982. While it is not surprising that a station at the northern limit of the Antarctic region should hold the regional temperature record, the observed temperature was exceptional even for Signy, exceeding the second highest ranked temperature in the record by 1.8 ∘ C. Only 1% of monthly maximum temperatures in the Signy record exceed 15 ∘ C. de los Milagros Skansi et al (2017) considered possible causes of this extreme event and suggested that it was driven by a combination of exceptional warm advection together with a local föhn effect. In this article, we examine these mechanisms in greater detail.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…A few days before the Atacama flood, most surface stations along the western border of South America from 20 • S to 40 • S experienced high temperatures close to all time records (Barrett et al, 2016). Almost simultaneously, Esperanza station (6324 ′ S, 5659 ′ W, 13 m) located at the tip of the Antarctic Peninsula registered the highest temperatures ever recorded for continental Antarctica (Skansi et al, 2017) (17.5 • C on 24 March 2015, see Figure S1b). This extreme Antarctic heat wave triggered a significant melting on the Larsen C ice sheet (Munneke et al, 2018) and was ultimately traced to foehn-induced warming that resulted from a landfalling atmospheric river (Bozkurt et al, 2018).…”
Section: Introductionmentioning
confidence: 78%
“…The event occurred just at the onset of the strong 2015–2016 El Niño event (between 18 and 27 March 2015), at the same time that the west coast of South America (northern, central, and southern Chile) was experiencing a series of extreme hydrometeorological events (Barrett et al, ; Bozkurt et al, ). Based on careful evaluation of several pieces of evidence (e.g., quality of observation, type and calibration of equipment, and foehn occurrence) by an international evaluation committee within the World Meteorological Organization Commission for Climatology, this extreme observation was certified as the highest temperature recorded for the Antarctic continent (Skansi et al, ).…”
Section: Introductionmentioning
confidence: 99%